Workforce Commitment in Malaysian Government Frontline Agencies - Mooi, Wah Kian (2016)
The primary purpose of this study is to determine the level of frontline employees’commitment and identify the different factors that affect this commitment level. The problem statement, compiled from real life happenings based on feedback from the general public, shows that the target Public Departments are experiencing a sharp increase in public complaints about the delivery and quality of public services. This, directly and indirectly, shows both a slag and a lag of commitment level of the Civil servants in Malaysia. The research methodology provides a framework of an organized and systematic approach to understanding and resolving the issues discussed in this study, based on core features identified in the literature review. Despite the availability of many scales to measure organizational commitment, the instrument adopted here is the Alan and Meyer’s Organizational Commitment Scale - Michigan Organizational Assessment Questionnaire, Maslach Burnout Inventory (MBI), Minnesota Job Satisfaction Questionnaire (MSQ).Out of a total of 700 questionnaires distributed to Kuala Lumpur City Hall, Kuala Lumpur Police and Kuala Lumpur Public Work Department, 547 returned usable questionnaires were processed, and the results tabulated, analysed and interpreted. The overall findings show that the civil servants in the said target agencies and departments were comfortable in their current employment as there was no intention to leave. The general conclusion suggests that the surveyed Malaysian frontline workforce has identified itself well as civil servants, but with little obligation to remain loyal despite some complaints about current employment conditions. Nevertheless, they did not feel stressful or burnt out, and they had no intention to leave the services. This study recommends that, for frontline civil servants to be more committed to their respective organizations, their respective management should focus on factors such as decision making responsibility, resource adequacy, effective communication, challenging job and job satisfaction in order to induce their frontline employees to be committed in the delivery of effective and effective public services on time and every time, assuming the job stability in government service as a given ceteris paribus.